Anarchist Acts Against the Implementation of Local Election which Resulted in Social Impacts on Opposition Groups (Case Study in Kaur District) - Rahman, Malik Akbar Mulki (Law Research Review Quarterly, 2018)
In reality there are still various problems arising from the impact of the elections in the form of discrimination against opposition teams, such as the losing opposition team when they want to apply for work as honorary staff in the government field will experience difficulties due to the existence of revenge by the winning team, even the most saddening impact that is, when an official with a strategic position in government known by the team of the winning candidate does not support his team, a mutation from a strategic position to an ordinary staff will be carried out, even the most concerning is to be transferred as a staff member who does not fit his area of ​​expertise by being replaced by a new person from the team the winning candidate who does not have a better ability than the previous officials, causing social disappointment and jealousy towards the government which led to demonstrations to demand that the regional head resign from office with anarchist action. The purpose of this research is to create harmony and kinship between the community and government officials in developing their regions in order to create a peaceful life. The research method used in this study uses descriptive qualitative methods with literature study techniques. The study in this research focuses on the process of implementing local elections that lead to anarchist actions. In addition, this study also outlines the factors causing anarchist acts, discrimination and so on.